New computational paradigms changing conceptions of what is computable - Cooper, S. B. (S. Barry); Lowe, Benedikt; Sorbi, Andrea 1956- (Springer, 2008)
Examines developments in the theory and practice of computation from a mathematical perspective, with topics ranging from classical computability to complexity, from biocomputing to quantum computing. This book covers topics in computability theory such as relative computability, theory of numberings, and domain theory.